Blood Neutrophil Dynamics in Periparturient Murrah Buffaloes - Mohapatra, Arpita; Dang, Ajay Kumar (Indian Journal of Dairy Science, 2017)
Neutrophils play an important role around parturition. To evaluate relationship between cytological changes occurring in blood neutrophils and their functionality during peripartum period, blood samples were collected from 10 Murrah buffaloes (-15 to +15 day) at weekly interval. Total leukocyte count (TLC) and percent neutrophils were significantly higher (PË‚0.05) on the day of calving. Morphological features were assessed using both light and scanning electron microscopy (SEM). Blood neutrophils on different peripartum days showed a multi-lobed and matured nucleus as compared to band shaped nucleus of partum. SEM revealed that blood neutrophils had a more ruffled surface on different peripartum days compared to the neutrophils derived on the day of calving. Phagocytic activity (PA) of neutrophils isolated from blood of peripartum buffaloes were significantly lower (P<0.05) on day of calving compared to other peripartum days. Relative messenger RNA (mRNA) expression of Toll like receptors (TLR 2, TLR 4) and interleukin-8 (IL-8) genes in blood neutrophils of Murrah buffaloes was found to be significantly (P<0.05) higher on different peripartum days compared to the day of calving. The present study showed that on the day of calving although vast number of neutrophils poured into the blood stream but more of them are immature ones, having poorly developed surface receptors, compromised phagocytic activity and diminished expression of immunologically important neutrophil specific genes.